Innovative Technologies in Seafood Processing - Ozogul, Yesim (Boca Raton : CRC Press LLC, 2019)
While conventional technologies such as chilling and freezing are used to avoid deteriorative processes like autolytic and microbial spoilage of seafood, innovative technologies have also been developed as a response to economic and environmental demands. Innovative Technologies in Seafood Processing gives information on advances in chilling, freezing, thawing, and packaging of seafood and also updates knowledge of novel process technologies (high-pressure processing, irradiation, ultrasound, pulsed electric field, microwave and radio frequency, sous vide technology, novel thermal sterilization technologies, ozone and nanotechnological applications, and other innovative technologies such as cold plasma, ohmic heating, infrared heating supercritical carbon dioxide, and high-intensity pulsed light) for the seafood industry. Features Reviews novel process technologies applied in the seafood industry Highlights processing effects on product quality and safety of treated seafood Focuses on the development of safe and effective natural antimicrobials and additives Assesses alternative techniques to utilize fish discards and waste as high value products Further it highlights aspects related to quality of seafood treated with these innovative technologies, effect on food constituents, possible risk, security/safety both of seafood and consumers, the environmental impact, and the legislative aspects. The book also addresses the growing international environmental concern for fish discards and fish waste generated in the seafood processing industries by including a chapter, Advances in Discard and By-Products Processing, which assesses alternative techniques to utilize fish discards and waste as high value products. This book will be of value to researchers and technicians in the food technology area, especially those dealing with seafood.
Chapter 10: Ozone Application in Seafood ProcessingChapter 11: Effect of Natural Preservatives on Chemical Changes Related to Quality and Shelf Life in Processed Aquatic Foods; Chapter 12: Application of Natural Antimicrobial Strategies in Seafood Preservation; Chapter 13: Sous Vide Technology; Chapter 14: Nanotechnological Applications; Chapter 15: Novel Thermal Sterilization Technologies in Seafood Processing; Chapter 16: Advances in Discard and By-product Processing; Chapter 17: Other Innovative Technologies in Seafood Processing; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Life Sciences / Biology / Marine Biology; TECHNOLOGY / Food Science; Fishery processing